RANCANG BANGUN SISTEM MONITORING PADA HIDROPONIK NFT (NURTIENT FILM TEHCNIQUE) BERBASIS IOT - Pamungkas, Lindu; Rahardjo, Pratolo; Raka Agung, I Gusti Agung Putu (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p2, 2021)
The use of hydroponics is an effective way to carry out farming activities without the need for large tracts of land. Hydroponics requires extra supervision to be able to produce plants with good quality. There are three main parameters in hydroponics, namely the amount of dissolved nutrient content, the pH level in water, and the water suhue level. To provide convenience in conducting surveillance, this research designed an IoT-based NFT hydroponic monitoring system. The use of TDS sensors, pH sensors, and temperatur sensors DS18B20 in this study are used to measure any changes that occur in the three parameters. Sensor data will be processed by Arduino Mega 2560 and sent to Firebase databases via NodeMCU ESP8266 which is connected to the internet network, so users can supervise anytime and anywhere through the android mobile application.